Accessing Intraabdominal Abscess for Percutaneous Drainage Using a Trocar Only Technique to Maneuver Intervening Bowel - Hussain, Hafsa; Deek, Feras; Efridi, Wajahat; Shaikh, Azim; Syed, Mubin (Indian Journal of Radiology and Imaging, 2022)
Conventional approaches to the drainage of abscess surrounded by bowel contraindicate percutaneous drainage and often involve more invasive laparotomy. We attempt to demonstrate the use of an image-guided blunt trocar to navigate obstructive bowel and access abdominal abscess. This report presents the use of a blunt trocar to safely maneuver obstructive bowel and perform successful percutaneous drainage of intraabdominal abscess in two separate cases: one presenting a left lower quadrant diverticular abscess and the other presenting an abscess in the right lower quadrant. Thus, traversing obstructive bowel using a blunt trocar under computed tomography-guidance allows for percutaneous drainage of an intraabdominal abscess, and provides a safer and more effective alternative to more invasive procedures.
Keywords: abdominal; abscess; access; bowel; CT-guided; drainage; hydrodissection; obstructive; percutaneous; trocar